PENGARUH TINGKAT PENDIDIKAN, PENGALAMAN KERJA DAN PENEMPATAN TERHADAP KINERJA KARYAWAN PADA PT. BANK RIAU KEPRI CABANG TELUK KUANTAN - Reza, Wahyu Prima; Musfar, Tengku Firli; ', Marzolina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine how the effect of the level of education, work experience and placement on the performance of employees at PT. Bank Riau Riau Kepri Cabang Teluk Kuantan. As for the population in this study were all employees of PT.Bank Riau Riau Kepri Cabang Teluk Kuantan totaling 55 employees. While the sampling is done by making all employees as a sample. Analysis of the data used is descriptive analysis with quantitative analysis tools that multiple linear regression with SPSS version 18:00. From the testing that has been done, simultaneous test shows that the level of education, work experience and placements influence on the performance of employees, while the partial test showed that the level of education, work experience and placement partial effect on the performance of employees. Employee performance needs to be optimized to the planned objectives can be achieved. For that is expected to the leading companies that pay attention to the harmony of communication that exists among employees at work. For example, by giving more work done in groups so that communication among employees can be properly maintained. Thus employees are expected to work with the maximum. With that employees will feel heavy for leaving the company.Keyword : Education, Work Experience, Placement and Performance Employees.